Active control of supersonic transport aeroelastic oscillations using high-fidelity equations. (30th June 2019) - Guruswamy, Guru
Abstract: A higher order computational procedure to alleviate aeroelastic oscillations by using active control surfaces is addressed. Flow is modeled using the high-fidelity Navier–Stokes (NS) equations, compared to the current use of the low-fidelity linear theory to design active controls. An active control module is embedded into a general-purpose NS flow solver developed for full aircraft configurations. The structure is modeled using the modal equations of motion, and existing active control equations based on the energy approach are utilized. Previously established transonic small perturbation theory and wind tunnel experiments are considered for validating. The use of active controls for next generation supersonic transport aircraft is demonstrated.